PTSD symptoms as a potential mediator of associations between military sexual assault and disordered eating. Issue 3 (4th May 2023) - Sandhu, Danielle; Dougherty, Elizabeth N.; Haedt-Matt, Alissa
ABSTRACT: Despite increasing rates of sexual assault in the military and high rates of disordered eating and post-traumatic stress disorder (PTSD) among veterans, little is known about how these constructs are related. This study examined whether PTSD symptoms mediate the relation between military sexual assault and disordered eating among female veterans. United States female veterans ( N = 98) completed self-report measures assessing military sexual assault, PTSD, and disordered eating. Results indicated that military sexual assault was associated with higher PTSD symptoms and disordered eating. PTSD symptoms did not mediate the relation between military sexual assault and overall levels of disordered eating. However, PTSD symptoms fully mediated the relation between military sexual assault and the Bulimia and Food Preoccupation subscale of the Eating Attitudes Test-26. Findings suggest that military sexual assault may contribute to the development of bulimia nervosa symptoms indirectly through PTSD symptoms. Thus, the findings do not support a global relationship between trauma and all facets of disordered eating, but demonstrate a relationship between PTSD and bulimia nervosa symptoms, with purging potentially functioning as an emotion regulation strategy. Future longitudinal studies are needed to establish temporal precedence of these associations.